2010
DOI: 10.1111/j.1469-8749.2009.03601.x
|View full text |Cite|
|
Sign up to set email alerts
|

Thickened saliva after effective management of drooling with botulinum toxin A

Abstract: AIM The aim of this study was to evaluate the rheological properties of saliva after submandibular botulinum toxin type A (BoNT-A) injections.METHOD We enrolled 15 children (11 males and six females; age range 3-17y, mean age 9y 10mo) diagnosed with spastic (n=9) or dyskinetic (n=6) quadriplegic cerebral palsy (CP); Gross Motor Function Classification System level IV or V; and two children with intellectual disability (IQ <70) who experienced moderate to severe drooling. Salivary flow rate and drooling quotien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
4
33
0
1
Order By: Relevance
“…One patient had swallowing problems due to the diffusion of BTX-A into the surrounding muscles, leading to temporary muscle weakness. This is a known adverse effect of BTX-A; it has been documented in other studies as well [12,13]. In a larger study (175 BTX-A injections), dysphagia was reported in 3% of injections [12], which is approximately the same range as in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One patient had swallowing problems due to the diffusion of BTX-A into the surrounding muscles, leading to temporary muscle weakness. This is a known adverse effect of BTX-A; it has been documented in other studies as well [12,13]. In a larger study (175 BTX-A injections), dysphagia was reported in 3% of injections [12], which is approximately the same range as in our study.…”
Section: Discussionsupporting
confidence: 88%
“…In a larger study (175 BTX-A injections), dysphagia was reported in 3% of injections [12], which is approximately the same range as in our study. In a study of 17 patients, swallowing problems were documented in 41% (7/17) of children with cerebral palsy who received injections of BTX-A to the submandibular glands, but the authors proposed this was mainly due to a thicker composition of saliva [13]. Excessive dryness of the mouth is also possible after BTX-A treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…Higher salivary viscosity after BoNT-A injections may result in problems with intraoral processing of (solid) food. 20,21 Indeed, we found a significant association between increased salivary viscosity and the occurrence of adverse effects. Concerning oral motor function, the second potential cause of BoNTrelated problems is the diffusion of the toxin outside the salivary gland leading to muscle weakness.…”
Section: Discussionmentioning
confidence: 54%
“…d Six studies reported on the same cohort of patients: Jongerius et al. (A) and (B) reported on two different outcome measures in the same cohort of patients; Scheffer et al (B) later incorporated the Jongerius et al patients as well as Scheffer et al 2010 (A) patients; Erasmus et al 25,31 performed secondary analyses on the Scheffer et al (B) cohort of patients. SMG, submandibular gland; BoNT, botulinum toxin; NS, not specified; GA, general anaesthetic; MU, mouse units of BoNT‐B; PG, parotid gland.…”
Section: Resultsmentioning
confidence: 99%